Pemanfaatan Angle Fotografi Pada Foto Dokumentasi - M.Ifran Sanni; Yudi Dian; Ramdhan Ramdhan (UNIVERSITAS RAHARJA, 2016)
Since its inception photography has become on indispensable part of human life. There are lpt of beautiful momentshas successfully captured by this photograph activity. Capturing human activities whereher located and freeze in a photpgraphic word made this event veri interesting to dol a photograph is able to express our fellings, human relationships to show the beauty of divine creation. Photography techniques there are rules contained in the art of photography it self. Learning by techniques of photography and often practice, we able understand the aesthetics of a photography to draw a great picture and interesting. In addition, we will be trained to convey a message through media photograph to everyone.